HPB cancers in older patients | inclusion of older/senior patients in clinical trials. (March 2021) - Backen, Alison; Lamarca, Angela; Hubner, Richard A.; McNamara, Mairéad G.; Valle, Juan W.
Abstract: Liver, biliary tract and pancreatic cancers are increasingly diseases of older people and the global population is aging. 'Older/senior' patients are a heterogeneous group who vary widely in their general health, physical reserve and degree of dependence on others. Cancer is not the only disease that becomes more prevalent in old age, which means older/senior patients may also have comorbidities and lower resilience. The use of chemotherapy decreases as age increases. Chemotherapy treatment regimens may require modification to reduce toxicity, which is more common in older/senior patients. The effect this has on treatment efficacy is not fully understood. Older/senior patients are not represented well in clinical trials which makes estimating benefit for these patients challenging. Medicine demands that new drugs are rigorously tested and evaluated before use, yet clinicians are treating older/senior patients on the basis of extrapolating from randomised controlled trials which actively exclude comorbidities and older patients. This review considers the current situation and the value of retrospective analyses and real-world evidence to plug the older/senior patient 'data gaps'. Moving forwards it is essential to broaden clinical trial inclusion criteria to include more older/senior people. The use of appropriate geriatric assessments may help selection of older patients who are fit enough for more rigorous treatment regimens, alongside effective methods of predicting and managing treatment toxicities. The ability to see past the numerical age of a person and offer appropriate therapeutic choices to individual patients in clinic, is an important skill for younger (and not so young) Medical Oncologists to learn.